ECOWAS COMMON CURRENCY: HOW PREPARED ARE ITS MEMBERS? - Mati, Sagiru; Civcir, Irfan; Ozdeser, Hüseyin (Investigación Económica, 2019)
ABSTRACT This study operationalizes the Optimum Currency Area (OCA) to investigate the preparedness of Economic Community of West African States (ECOWAS) members to form a Monetary Union (MU). Inflation and output models are estimated, with the sample 1988:01 to 2017:12 for the former and 1967 to 2016 for the latter. Analyses of ECOWAS convergence criteria, impulse responses, variance decompositions and correlations of shocks of these two models, reveal that the shocks across the ECOWAS members are asymmetric. The conclusion is that ECOWAS members as a whole are not well-prepared and therefore a full-fledged pan-ECOWAS MU is not advisable. It is also found that members of the European Monetary Union (EMU) tend to be a better fit for OCA than the ECOWAS members. The study recommends various courses of action such as fostering coordination among Central Banks of ECOWAS members, and providing a fund to serve as an incentive for countries that may incur cost rather than benefit if the single currency is created. LA MONEDA COMÚN DE LA ECOWAS: ¿CUÁN PREPARADOS ESTÁN SUS MIEMBROS? RESUMEN Utilizamos el Área Monetaria Óptima (AMO) para indagar cuán preparados están los miembros de la Comunidad Económica de Estados de África Occidental (ECOWAS, Economic Community of West African States) para formar una Unión Monetaria (UM). Estimamos modelos de inflación y producto con datos de 1988:01-2017 y 1967-2016 respectivamente. Los análisis de criterios de convergencia, impulso-respuesta, descomposición de varianza y correlación de choques de estos modelos revelan que los choques entre estos países son asimétricos. Concluimos que estos países no están bien preparados y, por tanto, una UM pan-ECOWAS no es aconsejable. Además, los integrantes de la Unión Monetaria Europea (UME) tienden a satisfacer mejor una AMO que los de ECOWAS. Nuestro análisis recomienda fortalecer la coordinación entre los bancos centrales de la ECOWAS y un fondo que incentive a los países que incurran en costos en lugar de beneficios si se crea la moneda única.